Role of ascomycete and basidiomycete fungi in meeting established and emerging sustainability opportunities: a review - Wan Mohtar, Wan Hanna Melini; Wan-Mohtar, Wan Abd Al Qadr Imad; Zahuri, Afnan Ahmadi; Ibrahim, Mohamad Faizal; Show, Pau-Loke; Ilham, Zul; Jamaludin, Adi Ainurzaman; Abdul Patah, Muhamad Fazly; Ahmad Usuldin, Siti Rokhiyah; Rowan, Neil (Taylor & Francis, 2022)
Fungal biomass is the future’s feedstock. Non-septate Ascomycetes and septate Basidiomycetes, famously known as mushrooms, are sources of fungal biomass. Fungal biomass, which on averagely comprises about 34 protein and 45 carbohydrate, can be cultivated in bioreactors to produce affordable, safe, nontoxic, and consistent biomass quality. Fungal-based technologies are seen as attractive, safer alternatives, either substituting or complementing the existing standard technology. Water and wastewater treatment, food and feed, green technology, innovative designs in buildings, enzyme technology, potential health benefits, and wealth production are the key sectors that successfully reported high-efficiency performances of fungal applications. This paper reviews the latest technical know-how, methods, and performance of fungal adaptation in those sectors. Excellent performance was reported indicating high potential for fungi utilization, particularly in the sectors, yet to be utilized and improved on the existing fungal-based applications. The expansion of fungal biomass in the industrial-scale application for the sustainability of earth and human well-being is in line with the United Nations’ Sustainable Development Goals.